The factors influencing customer satisfaction in online shopping : a case study in UiTM Sabah / Noor Amirah Tompang and Nursyafira Fatini Rizuan - Tompang, Noor Amirah; Rizuan, Nursyafira Fatini (2016)
Nowadays online shopping has become very popular and familiar. This is because many people use the Internet as an alternative to purchase a product. According to the varies definition, in this study online shopping means the process of buying goods and services sold over the Internet. Internet shoppers among Malaysia are more likely to be young, affluent, highly educated and wealthy (Mohd Suki al., 2006). As we can see, online shopping becomes a trend among young people in Malaysia nowadays. Young people are the one who frequently uses the internet especially, for the students who are in the higher education institution. Based on the research done by Lim, Lim & Heinrichs (2005), most Malaysian between 20 to 25 years old are proving to do online shopping. In the research by Golden (2007), it is observed that students have much leisure time after class that they can use to surf the internet. By using the internet more, students' lives depend more on the internet and it encourages more online shopping. Customers tend to use online shopping because they can find many things cheaper in online store than traditional stores. Apart from that, online shopping offers the customer a wide range of products and services wherein he is able to compare the price quoted by different suppliers and choose the best deal from it. Internet marketing is conceptually different from other marketing channels and the internets are promoting a one to one communication between the seller and the end user with round the clock customer service. Today, business internet marketing is the fastest growing segment of online commerce. The major difference between traditional and online selling is the extent of interaction between the consumer and the seller. There is much more electronic interactivity with the consumer in the form of emails and FAQs. Through FAQs, the consumer's questions on shipment, payment, product, policies and other customer concerns can be addressed effectively. Usually the social network sites such as Facebook, Instagram and blogs play a part of communication technologies that serve as channels for retailers to sell their products and for the e-shopper to shopping through online. For example, the online retailer may use Facebook to promote and advertise their product due to easier to gain attention from many Facebook users. With the advancement of technology, it is important to recognize the customer's perception and expectation to ensure they gain their satisfaction in online shopping. Customer satisfaction is the ultimate result of meeting a consumer's expectation from the performance of products. Most satisfied customers normally have the intention to re-purchase the products if product performance meets his or her expectation. In this study, customers satisfactions are refer to the student's satisfaction.